(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2012)
Data about a new for flora of Ukraine moss species – Syntrichia laevipila Brid. is reported. Syntrichia laevipila was found within association Syntrichietum laevipilae Ochsn. 1928 on bark of old-growth trees in arboretum of Nikita Botanical Garden and in relict juniper-oak grove of “Mys Martjan” reservation (South Crimea, Ukraine).